Óleo essencial das folhas do Quimiotipo II de Lippia alba (MILL.) N. E. Brown: mecanismo de ação antimicrobiano em Staphylococcus aureus e atividade cicatrizante - Teixeira, Andrea Bessa (2015)
The Lippia alba is a medicinal plant widely used by the population for the treatment of various diseases. The chemical composition of essential oil presents qualitative and quantitative variation, ranking chemotypes. In Ceará, the chemotype II is recognized by the essential oil of L. alba (OELaII) contain high levels of limonene and citral. Wound healing involves cellular and molecular events that interact to occur reconstitution of the tissue. Bacterial contamination, mainly by S. aureus is one of the main factors that affect healing. The aim of this study was to investigate the OELaII mechanism of action of S. aureus and its healing activity. The mechanism of action was evaluated through the membrane changes in bacterial morphology and inhibition of virulence factors. The healing action was determined in vivo in experimental skin wounds through the area of ​​wound contraction, the clinical, histopathological and microbiological. The OELaII mechanism of action of S. aureus occurred by direct action on the cellular shell proven by irreversible changes in the permeability of the cytoplasmic membrane, as the results showed increased crystal violet uptake, release of nucleic acids and potassium efflux and damage the bacterial wall visualized by Atomic Force Microscopy. Along with this, inhibition of virulence factors highlighted in this study, may be associated with changes in gene expression, and to promote the hypothesis that OELaII modify the pattern of enzyme secretion, by altering the cell membrane. The results of the healing process, the groups treated with the formulations and OELaII OELaII base accelerated the healing process by promoting a significant increase in the percentage of wound contraction and epithelialization. The results showed that these groups during the treatment, a significant decrease in microbial population provide local favorable conditions by topical therapy aimed at the best results and the lowest possible time of the healing process. Therefore, the data of this study showed that OELaII is a healing agent of skin wounds, with high antimicrobial activity and that these biological activities reinforce the great potential of OELaII as a candidate for the development of a topical drug effective in the treatment of wounds in various clinical situations.